Hygienic assessment of the consumption of trans fatty acids by the population of the Omsk region - A. D. Chubarova; M. S. Turchaninova; N. V. Gogadze; E. A. Vilms; E. V. Shcherba (Фундаментальная и клиническая медицина, 2024)
Aim. Assessment of the content of trans-fatty acids in foods consumed by the population of the Omsk region and the values of their actual consumption.Materials and Methods. The results of laboratory studies of food products from the following groups were analyzed: fast food (hamburgers, french fries, chips); confectionery; oils, fats; meat products; dairy products (n=438). In product samples, the mass fraction of trans-fatty acid isomers was determined by gas chromatography. An assessment was made of the actual nutrition and consumption of trans fats by the inhabitants of the region using the method of analyzing the frequency of food consumption (n=441).Results. The median content of trans fats in the main food groups was 0.67% of total fat, which does not exceed the values recommended by WHO. There was a decrease in the content of trans-isomers in food products from 2.7% in the period 2016−2017. up to 1.0% in the period 2020−2021 However, there remains a significant health risk associated with the consumption of trans-fatty acids, due to the high proportion of samples exceeding the recommended levels (24.5±2.1%), to a greater extent the risk was determined by the consumption of confectionery. The median consumption of TFAs in the study population was 1.16 g, which is in line with the recommended norms. The proportion of people with excess recommended consumption was 10.2%.Conclusion. The results indicate an improvement in the situation related to the consumption of trans fats in 2016-2021 due to stricter requirements for their content in food products. It is necessary to conduct further research related to the assessment of the content of trans-isomers of fatty acids in the diet of various population groups to identify risk groups and priority food products - sources of trans fats.